A diversidade beta de comunidades de macroinvertebrados é menor em córregos degradados? Uma avaliação experimental - Libório, Rogério Aparecido (Universidade Federal de São Carlos, 2011)
Aiming to answer the question: preserved streams can sustain higher beta diversity than degraded streams? We estimated beta diversity of preserved and degraded streams during the rainy season of 2009 in pool and riffle areas using as substrate bags of leaf litter of tree species Talauma ovata. We analyzed the similarity in taxonomic composition of different mesohabitats using different indices of similarity (Sørensen, Morisita-Horn and Horn) and their corresponding estimators of diversity. Our study showed higher values of beta diversity in streams degraded when estimated by the similarity indices of Sørensen and Morisita-Horn. On the other hand the Horn index indicated no differences between the streams. This greater differentiation in faunistic composition between the different streams in degraded mesohabitats seems to be related to degradation of the riparian zone which favored the largest effect of hydrological disturbance due to increased volume of water especially in areas of pool resulting in elimination of taxa and increase local the dominance of more tolerant taxa, affecting beta diversity. This study paves the way for new understandings of the effects of degradation of riparian zones in streams, because the comparison between habitats within a given stream may provide a basis to assess their state of degradation, making possible new approaches to biomonitoring.
Keywords: Ecologia de comunidades; Macroinvertebrados aquáticos; Córregos; Mesohabitats; Biomonitoramento; Diversidade beta; Remansos e corredeiras; Índices de similaridade; Beta diversity; Macroinvertebrates; Pools and riffles; Similarity indices; Biomonitoring; CIENCIAS BIOLOGICAS::ECOLOGIA